Dynamic B0 shimming of the motor cortex and cerebellum with a multicoil shim setup for BOLD fMRI at 9.4T. Issue 5 (11th November 2019) - Aghaeifar, Ali; Bause, Jonas; Leks, Edyta; Grodd, Wolfgang; Scheffler, Klaus
Abstract : Purpose: We assessed how improved static magnetic field (B0 ) homogeneity with a dynamic multicoil shimming can influence the blood oxygen level dependent (BOLD) contrast to noise when echo planar imaging (EPI) sequence is used for a motor task functional MRI study. We showed that a multicoil shim setup can be a proper choice for dynamic shimming of 2 spatially distant areas with different inhomogeneity distributions. Methods: A 16‐channel multicoil shim setup is used to provide improved B0 homogeneity by dynamic slice‐wise shimming. The performance of dynamic B0 shimming was investigated in 2 distinct brain regions, the motor cortex and the cerebellum, in the same experiment during a finger‐tapping task. Temporal SNR (tSNR), geometric distortion of the EPIs, and results of an analysis with a general linear model before and after shimming with the multicoil were compared. Results: Reduced B0 deviation by 30% and 52% in the cerebellum and motor cortex, respectively, resulted in higher tSNR and a reduction of distortions in the EPI. Statistical analysis applied to the EPIs showed higher t values and increased number of voxels above significance threshold when shimming with the multicoil setup. Conclusions: Improved B0 homogeneity leads to higher tSNR and enhances the detection of BOLD signal.